Five-Year Prognosis After TIA or Minor Ischemic Stroke in Asian and Non-Asian Populations. (5th January 2021) - Hoshino, Takao; Uchiyama, Shinichiro; Wong, Lawrence K.S.; Kitagawa, Kazuo; Charles, Hugo; Labreuche, Julien; Lavallée, Philippa C.; Albers, Gregory W.; Caplan, Louis R.; Donnan, Geoffrey A.; Ferro, José M.; Hennerici, Michael G.; et al.
Abstract : Objective: To determine long-term vascular outcomes of Asian patients who experienced TIA or minor ischemic stroke and to compare the outcomes of Asian patients with those of non-Asian patients, in the context of modern guideline-based prevention strategies. Methods: This is a subanalysis of the TIAregistry.org project, in which 3, 847 patients (882 from Asian and 2, 965 from non-Asian countries) with a recent TIA or minor ischemic stroke were assessed and treated by specialists at 42 dedicated units from 14 countries and followed for 5 years. The primary outcome was a composite of cardiovascular death, nonfatal stroke, and nonfatal acute coronary syndrome. Results: No differences were observed in the 5-year risk of the primary outcome (14.0% vs 11.7%; hazard ratio [HR], 1.10; 95% confidence interval [CI], 0.88–1.37; p = 0.41) and stroke (10.7% vs 8.5%; HR, 1.17; 95% CI, 0.90–1.51; p = 0.24) between Asian and non-Asian patients. Asian participants were at higher risk of intracranial hemorrhage (1.8% vs 0.8%; HR, 2.23; 95% CI, 1.09–4.57; p = 0.029). Multivariable analysis showed that the presence of multiple acute infarctions on initial brain imaging was an independent predictor of primary outcome and modified Rankin Scale score of >1 in both Asian (HR, 1.91; 95% CI, 1.11–3.29; p = 0.020) and non-Asian (HR, 1.39; 95% CI, 1.02–1.90; p = 0.037) patients. Conclusion: The long-term risk of vascular events in Asian patients was as low as that in non-Asian patients, while Asian participants had a 2.2-fold higher intracranial hemorrhage risk. Multiple acute infarctions were independently associated with future disability in both groups. Classification of Evidence: This study provides Class I evidence that among people who experienced TIA or minor stroke, Asian patients have a similar 5-year risk of cardiovascular death, stroke, and acute coronary syndrome as non-Asian patients.